The Influence of Administrative Traditions and Governance on Private Involvement in Urban Climate Change Adaptation. - Klein, Johannes; Juhola, Sirkku (Review of Policy Research, 2018)
This qualitative study examines how administrative traditions and governance in two cities, New York City and Helsinki, have affected the interplay of public administration, the private sector, and citizens in climate change adaptation. The results show that both cities aim for an increased state‐market‐civil society interaction. However, their efforts have different points of departure and follow different trajectories. New York City's administration is within the Anglo‐American tradition of state‐market dualism, while the state‐market‐civil society interaction for adaptation is coordinated by newly created administrative organizations. This interaction has to be accommodated to the strong reliance on market mechanisms. Helsinki's administration has its roots in the welfare state administration with a strong role of the public administration. Increased state‐market‐civil society interaction results in a reduced influence of the public sector and the reliance on ad hoc projects and informal modes of cross‐sectoral cooperation.